A dual-reciprocity boundary element method for axisymmetric thermoelastostatic analysis of nonhomogeneous materials - Yun, Bao Ing (2013)
The problem of determining the axisymmetric time-independent temperature and thermoelastic displacement and stress fields in a nonhomogeneous material is solved numerically by using a dual-reciprocity boundary element technique. Interpolating functions that are bounded in the solution domain but that are in relatively simple elementary forms for easy computation are constructed for treating the domain integrals in the dual-reciprocity boundary element formulation. The proposed numerical approach is successfully applied to solve several specific problems.